PREFIXED VERBS OF MOVEMENT IN MODERN RUSSIAN (Лучшие интеллектуальные исследования, 2025)
Annotation. The article explores the prefix verbs of movement as a significant element of Russian word formation and semantics. The processes of their formation, features of use in speech, as well as their role in the transmission of spatial and temporal characteristics of the action are analyzed. Examples from language practice and recommendations on the study of this phenomenon in the educational process are given.